Numerical simulation of breast reduction with a new knitting condition. (2nd June 2016) - Lopes, Diogo; Clain, Stéphane; Pereira, Rui M. S.; Machado, Gaspar J.; Smirnov, Georgi; Vasilevskiy, Igor
Summary: Breast reduction is one of the most common procedures in breast surgery. The aim of this work is to develop a computational model allowing one to forecast the final breast geometry according to the incision marking parameters. This model can be used in surgery simulators that provide preoperative planning and training, allowing the study of the origin of the errors in breast reduction. From the mathematical point of view, this is a problem of calculus of variations with unusual boundary conditions, known as knitting conditions. The breast tissue is considered as a hyperelastic material, discretized with three‐dimensional finite elements for the body, whereas the skin is modelled with two‐dimensional finite elements on the curved surface. Although the model is of low precision, we show that it is sufficient for a satisfactory prediction of breast reduction surgery results, allowing an analysis of errors frequently performed during the surgery and giving an understanding of how to avoid or correct them. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We develop a computational model allowing to forecast the final breast geometry after a reduction surgery. The breast tissue is considered as a hyperelastic material with an additional model for the skin. Three‐dimensional finite elements for the body and two‐dimensional finite elements for the skin were implemented.